Efektivitas Asistensi Rehabilitasi Sosial Berbasis Residensial Terhadap Korban Penyalahgunaan NAPZA di Sentra “Insyaf” di Medan - Sami Hadisti Br Perangin Angin; Agus Suriadi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Rehabilitation is an important step to restore addicts to be productive and useful in society. Drug users who enter the rehabilitation center mostly experience low self-esteem and lack of a positive outlook on life, many of whom end up unable to carry out their social roles and social functions. Following the drug rehabilitation process is not everyone's dream, but unlike those who are already tired of their addiction, a rehabilitation center is the final choice to get out of addiction. This journal discusses the process of what activities are contained in one of the drug rehabilitation centers in the city of Medan, using the therapeutic community method in the rehabilitation process and how a drug addict can escape from the trap of opium and become a new person when completing the rehabilitation process. As well as the recovery programs provided by the center. The writing of this journal uses a casework method that emphasizes direct research on the object under study. Coupled with a mini project that involves a resident in the recovery proces.